PENERAPAN METODE STORY TELLING PADA PEMBELAJARAN BERBICARA DI KELAS III SEKOLAH DASAR (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2022)
This research is motivated by the low level of students' speaking skills. This study aims to improve the speaking skills of third-grade students at SDN Klender 03 Pagi through the application of audio-visual media. The subjects of this study were the third-grade students of SDN Klender 03 Pagi as many as 28 students. Data collection techniques used are tests, observations, interviews, field notes, and documentation. This research was carried out in 2 cycles with 2 actions in each cycle. The results showed that audio-visual media can improve students' speaking skills. This is indicated by an increase in the average value from before giving the action until the second cycle. The average valueobtained in the first cycle reached 56.70, and in the second cycle, the average value obtained increased to 88.50. In general, it can be concluded that the application of the storytelling method can improve the speaking skills of students in class III SDN Klender 03 Pagi.